2015
DOI: 10.1074/jbc.m114.620575
|View full text |Cite
|
Sign up to set email alerts
|

YbiB from Escherichia coli, the Defining Member of the Novel TrpD2 Family of Prokaryotic DNA-binding Proteins

Abstract: Background: YbiB belongs to the uncharacterized family of TrpD2 proteins. Results: YbiB binds to DNA with high affinity. The ybiB gene is under LexA control and induced by DNA-damaging agents. Conclusion: The TrpD2 proteins are a novel family of prokaryotic DNA-binding proteins. Significance: TrpD2 proteins may be part of the LexA-controlled SOS response in bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…However, the GN contains two domains of a DNA unwinding helicase (PF00271, PF06733) suggesting DNA interaction for these 452 sequences. Indeed, one representative, YbiB, has recently been characterized as a DNA-binding protein [ 12 ]. Altogether, this retrospective test case demonstrates the predictive power of GNNs, because the GNs are indicative of putative functions for all three clusters of homologs.…”
Section: Resultsmentioning
confidence: 99%
“…However, the GN contains two domains of a DNA unwinding helicase (PF00271, PF06733) suggesting DNA interaction for these 452 sequences. Indeed, one representative, YbiB, has recently been characterized as a DNA-binding protein [ 12 ]. Altogether, this retrospective test case demonstrates the predictive power of GNNs, because the GNs are indicative of putative functions for all three clusters of homologs.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that the cells maintained a consistent intracellular concentration of reduced thiols, and that oxidation of the thiols by CrO 4 2only had the observable effect of decreasing growth(24). Hence, the metabolomics analysis reported herein of the samples both exposed and not exposed to CrO 4 2allow us to further test the(28)(29)(30)(31). No DNA repair and/or division genes had large negative gene fitness changes…”
mentioning
confidence: 82%
“…The motif-based ClusPro-PeptiDock peptide docking protocol was used for unbiased global peptide docking ( 56 ). A model of YbiB containing all loop regions was taken from the AlphaFold Protein Structure Database ( 57 , 58 ) and converted into the biological dimer by superposition on the available experimental YbiB structure (PDB: 4MUO) ( 41 ). This model was provided as receptor structure to ClusPro.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, in E. coli , the ybiB gene is part of a LexA-regulated operon, together with the dinG helicase gene. As LexA is the main suppressor of the SOS stress response, this suggests that YbiB may play a so far unknown role in the SOS stress response, which is activated upon DNA damage ( 41 ).…”
Section: Introductionmentioning
confidence: 99%